INFLUENCE OF LOG LENGTH ON THE PRODUCTIVITY OF WOOD HARVESTING AND TRANSPORTATION - Belisario, Aline Vianna; Fiedler, Nilton César; Carmo, Flávio Cipriano de Assis do; Lemos Moreira, Giselle (Floresta, 2022)
The selection of machines and the development of operating systems are the major challenge for reducing costs in harvesting and forest transportation. This work aimed to carry out a technical analysis of harvesting and forest transport activities in two different log lengths (6 and 7m). The operational cycles of the Harvester, Forwarder and combined road train vehicle in mechanized harvest areas were evaluated. The technical analysis was performed through studies of times and movements, determining the operational efficiency and productivity of the machines. According to the results, processing consumed most of the harvester's operational cycle, while in the forwarder, the most time was consumed 35,2 and 45,2 m³·he-1 and 42,84 and 75,42 m³.he-¹. The larger log size led to an increase in the productivity of the harvester by 28% and the forwarder by 48%. Among the studied models of road train vehicles, the one that showed the best results both in the analysis made with a length of 6 m and 7 m, was the dimensions with 2.35 m in width and 2.85 in height. These vehicles had a total gross weight of 63.52 tonnes for logs with a length of 6m and 69.17 tons for logs of 7m, with an 8.17% higher performance compared to 6m logs. With the obtained results it can be concluded that the increase in the length of the logs increased the productivity and the performance of the harvest and the forest transport.